Rectal tenesmus due to tumor invasion into the pelvic cavity responding favorably to antiarrhythmic drug therapy - Yoshino, Kazuho; Koizumi, Takahisa; Nakazato, Kenei; Nakagawa, Tomoki; Masuda, Ryota; Mikami, Mikio; Tokuda, Yutaka; Iwasaki, Masayuki (Gan to kagaku ryoho, 2012)
We experienced 3 patients(Cases 1, 3, and 4)with pelvic tumor-related rectal tenesmus showing favorable responses to antiarrhythmic drugs. Based on this experience, we administered antiarrhythmic drugs preferentially to 2 others with tumor derived rectal tenesmus(Cases 2 and 5), and again obtained favorable responses. These 5 patients(1 man, 4 women)were 28-89(mean 58)years of age. The primary lesion was cervical cancer in 3 patients, ovarian cancer in 1, and bladder cancer in 1. In the 3 with cervical cancer, the tumor had directly infiltrated the rectum and vulva. The patient with ovarian cancer had a residual tumor in the Douglas pouch postoperatively. The patient with bladder cancer had undergone total cystectomy and urinary diversion using an ileal conduit at another institution. All 5 patients complained of a frequent desire to defecate without feces(rectal tenesmus). Their rectal tenesmus was attributed to pelvic neurological dysfunction around the rectum. Drug therapy was initiated with oral mexiletine hydrochloride(Mexitil)150 mg in 3 divided doses in 4 patients and with continuous infusion of intravenous lidocaine 2%(Xylocaine)500mg/day in the other(Case 2). None had adverse reactions; all 5 experienced palliation of symptoms and improved quality of life.